2016
DOI: 10.1515/hsz-2016-0190
|View full text |Cite
|
Sign up to set email alerts
|

Common therapeutic strategies for prion and Alzheimer’s diseases

Abstract: A number of unexpected pathophysiological connections linking different neurodegenerative diseases have emerged over the past decade. An example is provided by prion and Alzheimer's diseases. Despite being distinct pathologies, these disorders share several neurotoxic mechanisms, including accumulation of misfolded protein isoforms, stress of the protein synthesis machinery, and activation of a neurotoxic signaling mediated by the cellular prion protein. Here, in addition to reviewing these mechanisms, we will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Collectively, these data suggest that PrP Sc could be an inconvenient pharmacological target in prion diseases [ 22 ]. Targeting PrP C could be an alternative therapeutic strategy [ 23 , 24 ]. In fact, compounds directed against PrP C may produce the dual effect of interfering with the replication of multiple prion strains, and inhibit their neurotoxicity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data suggest that PrP Sc could be an inconvenient pharmacological target in prion diseases [ 22 ]. Targeting PrP C could be an alternative therapeutic strategy [ 23 , 24 ]. In fact, compounds directed against PrP C may produce the dual effect of interfering with the replication of multiple prion strains, and inhibit their neurotoxicity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperphosphorylation of tau depends on the A␤-PrP interaction (17). Therefore, understanding the A␤-PrP pathway will open new therapeutic strategies by targeting the A␤-PrP interaction (18).…”
mentioning
confidence: 99%
“…Collectively, these data challenge the concept that targeting exclusively PrP Sc replication is a convenient therapeutic strategy in prion diseases. A possible complementary approach could be to also target neurotoxic pathways mediated by PrP C . We have previously described the DBCA, a cellular assay based on the intrinsic cytotoxic effects of PrP molecules carrying mutations in the central region of the protein .…”
Section: Figurementioning
confidence: 99%
“…[7] Collectively,t hese data challenge the concept that targeting exclusivelyP rP Sc replication is ac onvenient therapeutic strategy in prion diseases.Apossible complementary approach could be to also target neurotoxic pathways mediated by PrP C . [8] We have previously described the DBCA, ac ellular assay based on the intrinsic cytotoxic effects of PrP molecules carrying mutations in the central region of the protein. [9] Multiple previouss tudies indicated that this assay is au seful tool to study PrP-mediatedn eurotoxic pathways, as well as to identify and characterize novel anti-prionc ompounds.…”
mentioning
confidence: 99%